2013
DOI: 10.1073/pnas.1305230110
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin blunts social vigilance in the rhesus macaque

Abstract: Exogenous application of the neuromodulatory hormone oxytocin (OT) promotes prosocial behavior and can improve social function. It is unclear, however, whether OT promotes prosocial behavior per se, or whether it facilitates social interaction by reducing a state of vigilance toward potential social threats. To disambiguate these two possibilities, we exogenously delivered OT to male rhesus macaques, which have a characteristic pattern of species-typical social vigilance, and examined their performance in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
155
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(176 citation statements)
references
References 54 publications
18
155
3
Order By: Relevance
“…Given the similarities between monkeys and humans in the neural circuitry underlying social cognition (19), the rhesus macaque could be an ideal animal model to examine the effects of OT. To date, only a few studies have investigated the behavioral consequences of OT administration in monkeys (20)(21)(22)(23)(24)(25). Consistent with the human literature, these studies have found that intranasal administration of OT affects social behavior and cognition in monkeys, Significance Oxytocin (OT), a mammalian hormone, may serve as a treatment for psychiatric disorders because of its beneficial effect on social behavior.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Given the similarities between monkeys and humans in the neural circuitry underlying social cognition (19), the rhesus macaque could be an ideal animal model to examine the effects of OT. To date, only a few studies have investigated the behavioral consequences of OT administration in monkeys (20)(21)(22)(23)(24)(25). Consistent with the human literature, these studies have found that intranasal administration of OT affects social behavior and cognition in monkeys, Significance Oxytocin (OT), a mammalian hormone, may serve as a treatment for psychiatric disorders because of its beneficial effect on social behavior.…”
mentioning
confidence: 83%
“…This is similar to the dose previously found to affect socially relevant behavior in monkeys (e.g., refs. [20][21][22] and humans (e.g., refs. 8,15,16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who increase their number of grooming partners in subsequent months experience a more rapid decrease in fGC levels than females that fail to do so, perhaps because increased grooming allows 'bereaved' females to repair the damage to their grooming network [36]. The link between stress and social attachment may occur, in part, because stress prompts the release of the peptide oxytocin (OT), a hormone that motivates attachment, trust and pair-bonding behaviour (see below) [37][38][39] and suppresses social wariness [40].…”
Section: The Adaptive Value Of Social Bondsmentioning
confidence: 99%
“…One relatively basic source of variation in cooperative potential is via neuromodulatory effects on neural circuits mediating social bonding [40,108]. For example, OT plays a crucial role in mammalian social behaviour.…”
Section: Neuromodulatory Sources Of Variation In Cooperative Potentialmentioning
confidence: 99%